126k views
0 votes
Determine the solution to f(x) = g(x) using the following system of equations: f(x) = 3x + 12 g(x) = -9.5x - 13

User Alectogeek
by
5.0k points

2 Answers

2 votes

Answer:

-2

Explanation:

User Bilal Qandeel
by
5.1k points
3 votes
Answer:

x=2

Step by step:
f(x)=g(x)

3x+12= -9.5x-13 simplifies to the equation below

3x+9.5x= -13-12

12.5x= -25
next, divide by 12 on both sides to isolate the variable, x.

12.5x/12 = -25/12

x=-2

to check: 3(-2)+12= -95x(-2)-13
-6+12= 19-13
6=6 ✅
User Milla Well
by
4.9k points